2010
DOI: 10.1002/cphc.201000882
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemistry of Carbon Nanotubes

Abstract: This Minireview is a critical survey of results accumulated during the last decade on the characterization of carbon nanotubes using a combination of electrochemical and spectroscopic methods. The article updates earlier reviews on the topic with special emphasis to recent progress in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 128 publications
(275 reference statements)
2
34
0
Order By: Relevance
“…For these reasons, the importance of spectroelectrochemistry (SEC) must be highlighted. A single SEC experiment provides simultaneous electrochemical and spectroscopic information about a chemical system, allowing the study of a wide range of processes from, at least, two different points of view . Furthermore, the sum of the two types of information is not a simple addition, providing a synergistic effect between optical and electrical signals that helps to explain the electrode process.…”
Section: Whatmentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons, the importance of spectroelectrochemistry (SEC) must be highlighted. A single SEC experiment provides simultaneous electrochemical and spectroscopic information about a chemical system, allowing the study of a wide range of processes from, at least, two different points of view . Furthermore, the sum of the two types of information is not a simple addition, providing a synergistic effect between optical and electrical signals that helps to explain the electrode process.…”
Section: Whatmentioning
confidence: 99%
“…As can be deduced, different electrochemical techniques can be used and different spectral regions can be analyzed, depending on the system studied and the desired information to be obtained . All these factors highlight the usefulness and versatility of SEC.…”
Section: Whatmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemistry and Raman spectroscopy have been combined in the spectro-electrochemical study of the state of CNTs and their composites, supported on solid substrates, under applied potentials. [40][41][42][43][44] Very recently, Ibañez et al 45 reported the use of Raman spectro-electrochemistry to study charge transfer processes at the ITIES, leading to the possibility of studying the state of CNTs and graphene during mediation of heterogeneous electron transfer at the ITIES; as the interfacial ET initiated charge transfer will result in a change in the Fermi-level of the assembled carbon nanostructures, thus doping them. All of these phenomena are of interest in electro-catalytic reactions, proton-coupled electron transfers and energy storage using the nanostructured organic/water interface.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Developments in Raman spectroelectrochemistry have highlighted this technique as one of the best to characterize and study different materials and processes in many fields. [38][39][40][41][42] In the present work, most of the experiments were performed using UV-vis absorption spectroelectrochemistry, although Raman spectroelectrochemistry provided suitable information in the study of particular systems, as for example, carbon nanotubes. One of the main highlights of the new bipolar device is its easy assembly.…”
mentioning
confidence: 99%